Accuracy of MRI vs ultrasound in the diagnosis of placental adhesive disorder - Hoda A Kareem Ahmed; Ahmed Abd-Elrady Ahmed; Khaled Abdallah Ahmed; Abdelgawad I Sakr (Wolters Kluwer Medknow Publications, 2020)
Background Placental adhesive disorder (PAD) is a fatal condition the rate of which has been rising progressively over the previous 50 years. PAD is the main reason for maternal morbidity and mortality and is now the most common cause of emergent postnatal hysterectomy. When transabdominal ultrasound (US) cannot conclusively exclude PAD as a diagnosis, the following imaging technique used is color Doppler ultrasonography. The gold standard investigation in high-risk patients is MRI in antenatal diagnosis. Aim The purpose of the study was to judge the accuracy of US and color Doppler vs MRI in the prenatal diagnosis of PAD. Patients and methods A prospective study included 50 patients aged from 20 to 40 years for high risk of developing or suspected to have PAD. The patients were evaluated by US and MRI and diagnosis was matched to postnatal outcomes. Results A total of 50 gravid women, the age of whom ranged from 20 to 40 years were included in the study. At gestational age that ranged from 20 to 39 weeks all gravid women were examined using MRI and US. The sensitivity of the US in the evaluation of PAD was 100%, the specificity 78.95%, positive predictive value 60%, negative predictive value 100%, and the overall accuracy was about 84%. The sensitivity of MRI in the evaluation of PAD was 100%, the specificity 89.47%, positive predictive value 75%, negative predictive value 100%, and the overall accuracy was about 92%. The P value for both US and MRI diagnoses of PAD was less than 0.001. Conclusion The US remains the primary imaging modality for assessment of the placenta. MRI has several exclusive features that make it superior in the evaluation of the placenta. Corresponding to the study, the most accurate US signs are the presence of lacunae and an unusual color Doppler imaging pattern. Corresponding to the study, the most reliable MRI signs are placental bands, heterogeneous placenta, and uterine bulging.